Time of Sowing Affects the Growth and Yield of Sesame in a Derived Savanna Agroecology of Southeastern Nigeria - Ogbonna, Peter Ejimofor; Umar-Shaba, Yakubu Gbacinku (2012)
A 2-yr study was conducted at the teaching and research farm of the Department of Crop Science, University of Nigeria, Nsukka to determine the effect of time of planting on growth and yield of sesame. The study determined the optimum time of sowing sesame in the derived savanna agroecology of southeastern Nigeria and identified high-yielding sesame accessions for the zone. Three sowing dates (July 22nd, August 22nd and September 22nd) were tested in 2009 while in 2010, the planting dates were June 22nd, July 22nd and August 22nd. Four sesame accessions (Zuru, NCRI-BEN 01M, 43-9-1 and NCRI-BEN 03L) were also evaluated in both years. Based on the results, time of sowing had a significant effect on growth and yield of sesame. Plant height, number of leaves, stem girth and number of branches per plant decreased with delay in time of sowing. Early sowing in the season significantly increased grain yield for all accessions. Grain yield decreased by 42% and 91% as sowing was delayed from July to August and September, respectively, in 2009 season. In 2010 season, grain yield decreased by 16% and 32% as sowing was delayed from June to July and August, respectively. Though seed yield in the accessions did not differ significantly, Zuru had the highest performance in both years. Among the climatic factors, rainfall appeared to contribute more to changes in performance across sowing dates.
Keywords: Sowing; Agroecosystem